2014
DOI: 10.1248/bpb.b14-00297
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Improved Carbon Tetrachloride-Induced Liver Fibrosis through Its Inhibition of the Activation of Hepatic Stellate Cells: Role of Autophagy

Abstract: Autophagy is involved in the activation of hepatic stellate cells (HSCs), which is the key process of liver fibrosis. We reasoned that chloroquine, based on its ability to inhibit autophagy, might exert beneficial effects in liver fibrosis. Liver fibrosis in rats was induced by carbon tetrachloride (CCl 4 ). Rats were divided into three groups, a normal control group (N group), model group (M group), and chloroquine group (CQ group). Liver fibrosis in the rats was evaluated by hematoxyline-eosin (H&E) and Mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Increased autophagy is observed in mice with liver injury induced by CCl 4 or thioacetamide, and loss of autophagic function by attenuated expression of Atg7 results in a reduction of fibrogenesis . The autophagy inhibitor chloroquine diminishes liver fibrosis in CCl 4 ‐treated mice and reduces the expression of profibrogenic genes in the mouse stellate cell line JS1 . Melatonin inhibition of autophagy has been recently reported to contribute to its protective effects against focal cerebral ischemia or liver ischemia–reperfusion .…”
Section: Introductionmentioning
confidence: 99%
“…Increased autophagy is observed in mice with liver injury induced by CCl 4 or thioacetamide, and loss of autophagic function by attenuated expression of Atg7 results in a reduction of fibrogenesis . The autophagy inhibitor chloroquine diminishes liver fibrosis in CCl 4 ‐treated mice and reduces the expression of profibrogenic genes in the mouse stellate cell line JS1 . Melatonin inhibition of autophagy has been recently reported to contribute to its protective effects against focal cerebral ischemia or liver ischemia–reperfusion .…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, four hits were tricyclic antidepressants (TCAs). The screen also identified chloroquine, which has been shown to reduce hepatic fibrosis in vivo 22.…”
Section: Resultsmentioning
confidence: 99%
“…The current data agree on those of He et al . [42] who demonstrated that CQ treatment of hepatic stellate cells in an in vivo liver fibrosis model diminished the expression and organization of α-SMA.…”
Section: Discussionmentioning
confidence: 99%